STRATEGI PEMERINTAH AFRIKA SELATAN MENGATASI DAMPAK NEGATIF KRISIS EROPA DI BIDANG PERDAGANGAN 2008-2014 - Laksmi Azizah Herawati (HI 15 UMY 471, 2015)
*471 South Africa is a republic located in southern Africa. It shares borders with Namibia, Botswana and Zimbabwe in the north, Mozambique and Swaziland in the northeast. South Africa is a democratic country with 50 million inhabitants and has the largest white population on the African continent. South Africa is a multiracial country with diverse cultures, religions and has 11 official languages. South Africa is also a country with the most advanced economy among other African countries. Since the end of apartheid, South African Republic has experienced sustained economic growth for 16 consecutive years. South Africa has a history of very good relations with Europe. Since 1994, South African and European countries which joined as the EU agreed to work together to build a good relationship and develop a comprehensive partnership based on trade, development and cooperation agreement (TDCA). The European Union is South Africa's largest partner and the main. In development aid, the EU accounted for â‚¬ 980 million for the period 2007-2013, with over â‚¬ 900 million comes from the European investment bank for the same period. Also in the field of trade, Europe receives 17% of South African exports. In the European Union (EU), five countries absorbed more than 80% of total South African exports to the Euro zone: Belgium, Germany, Italy, the Netherlands, and the UK. As the countries involved in world trade, South Africa is vulnerable to economic crisis. The Euro zone crisis that attacks European countries, bringing South Africa into one of the countries most adversely affected by the Euro zone crisis on the economy as a knock-on effect of fiscal consolidation in Europe, where it has led to reduced demand for exports from South Africa on goods and services and remittances, FDI and aid flows; through financial contagion in the form of spillovers through financial intermediaries and stock markets; and through the reduction of the value of the currency is pegged to the euro. The Euro zone economy is still in recession in the face of extensive fiscal austerity and tight bank lending conditions. So the impact arising from the Euro zone crisis has resulted in South Africa's trade balance deteriorated sharply in 2012 with a deficit of about ZAR 118 billion (ZAR 118 billion = US $ 11.8 billion), due to weak external demand from the Euro zone. Overall exports grew only about 0.8% in 2012, against 14.6% growth in imports. This research is focuses on the Strategy that South Africa government used to solve the impact of Euro zone Crisis on trade. Under qualitative approach, this research uses content analysis method. The framework uses the concept of export diversification. The result of this research shows that South Africa do export diversification strategy consist of horizontal diversification by increasing the production of manufacture sector, and export market diversification by searching a new market for South Africa product.